2002
DOI: 10.1128/aac.46.9.2797-2803.2002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Disinfectant Resistance Genes and Genetic Linkage with β-Lactamase Transposon Tn552among Clinical Staphylococci

Abstract: A total of 61 strains of Staphylococcus aureus and 177 coagulase-negative staphylococcal strains were isolated from the blood of patients with bloodstream infections and from the skin of both children under cancer treatment and human immunodeficiency virus-positive patients. The MIC analyses revealed that 118 isolates (50%) were resistant to quaternary ammonium compound-based disinfectant benzalkonium chloride (BC). The frequencies of resistance to a range of antibiotics were significantly higher among BC-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 29 publications
5
95
2
1
Order By: Relevance
“…Recent studies in Norway of human clinical staphylococcal isolates and food-related staphylococci suggest that there is a linkage between resistance to QACs and resistance to penicillin (23,24). In human hospital environments, it has been shown that staphylococci resistant to BC more frequently were resistant to certain antibiotics than were BC-sensitive isolates, indicating that the presence of either resistance determinant selects for the other during antimicrobial therapy and disinfection (23). In one of the herds, where QAC preparations were used daily for teat disinfection to prevent mastitis, milk samples were collected on several occasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Norway of human clinical staphylococcal isolates and food-related staphylococci suggest that there is a linkage between resistance to QACs and resistance to penicillin (23,24). In human hospital environments, it has been shown that staphylococci resistant to BC more frequently were resistant to certain antibiotics than were BC-sensitive isolates, indicating that the presence of either resistance determinant selects for the other during antimicrobial therapy and disinfection (23). In one of the herds, where QAC preparations were used daily for teat disinfection to prevent mastitis, milk samples were collected on several occasions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Norway of human clinical staphylococci and foodrelated staphylococci have shown that a linkage between QAC resistance and penicillin resistance occurs quite frequently (23,24). qacA/B and the ␤-lactamase gene (blaZ) were found to reside on common plasmids.…”
mentioning
confidence: 99%
“…Presence of IS257 was determined as described (Sidhu et al, 2002) with slight modifications. Primers based on the whole-genome sequence of Staph.…”
Section: Genotypingmentioning
confidence: 99%
“…We call attention to the fact that if the qacA/B gene is present at 80% of those MRSA, carefulness of controlling their survival in the hospital environment must be considered since the high prevalence of qacA/B gene might be either due selective pressure imposed by the large use of QACs disinfectant or due the cross-resistance and co-resistance between QACs and antibiotics (Sidhu et al 2002). Moreover it is necessary to have trained staff and use the best management practices for disinfecting, employing only the amount of disinfectant necessary to do the job to ensure the killing of microorganisms.…”
mentioning
confidence: 99%